(untitled) (Eurasian Research Bulletin, 2025)
This scientific work analyzes methodological problems encountered in tax collection through improving digitalization processes in the tax system. The possibilities of introducing digital technologies in tax administration, increasing transparency in relations with taxpayers, and expanding the tax base are highlighted. The need for integration of existing information systems, processing of large amounts of data, and the introduction of artificial intelligence and blockchain technologies is also substantiated. The study separately considers problems in increasing the efficiency of tax collection - insufficient development of methodological approaches, shortcomings in standardization, and issues related to data security